Reformulation of critical thinking in the Malaysian tertiary engineering education: An Islamic approach - Endut, M.N.A.-A. (Universiti Putra Malaysia, 2018)
The inculcation of critical thinking elements into the engineering undergraduate programme in Malaysia as one of the national Engineering Accreditation Council (EAC) priority has been included in nation's Vision 2020 to produce competent and innovative graduates with high ethical and professional standards. One of the major concerns raised in this inculcation model is the absence of Islamic critical thinking concept. The present concept of critical thinking taught in this country fails to connect with Islamic teaching and could lead to misunderstanding of the concept among Muslim engineering students. This paper aims to explore the elements of critical thinking embedded within the engineering curriculum in Malaysian higher learning institutions with particular interest to Muslim undergraduate students. The paper adopts the conceptual approach in stating the case for current implementation practices of critical thinking at higher learning and proposes a reformulation of how critical thinking based on Islamic teaching could be embedded into the formal learning institution elaborated through three main themes: a) the embedding of critical thinking in Malaysian faculties of engineering; b) the significance of elements of Islamic critical thinking to engineering education; and c) the accessibility of the main elements of Islamic critical thinking in engineering curriculum. Based on these themes, argument will be developed to illustrate the significance of Islamic critical thinking in relation to engineering education before finally reaching the approachable context on how to incorporate the elements of Islamic critical thinking which are yet to be identified within the content of Malaysian universities' engineering curriculum. Â© Universiti Putra Malaysia Press.